2020
DOI: 10.1016/j.bbrep.2019.100713
|View full text |Cite|
|
Sign up to set email alerts
|

Low level electricity increases the secretion of extracellular vesicles from cultured cells

Abstract: Exosomes, a type of extracellular vesicles, can be collected from the conditioned medium of cultured cells, and are expected to be used in disease therapy and drug delivery systems. However, since the yield of exosomes from conditioned medium is generally low, investigations to develop new methods to increase exosome secretion and to elucidate the secretion mechanism have been performed. Our previous studies demonstrated that activation of intracellular signaling including Rho GTPase and subsequent endocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…They demonstrated that ET did not impair viability of donor cells, and importantly, did not affect the quality and functionality of the collected EVs from each kind of donor cell tested. [87] These results are promising although further studies are needed to evaluate ET on other cell types. Moreover, the development of a well-defined methodology to apply ET to a higher number of cells will contribute to the general improvement of this novel technology for EV production.…”
Section: Improving the Ev-producer Cellsmentioning
confidence: 91%
See 1 more Smart Citation
“…They demonstrated that ET did not impair viability of donor cells, and importantly, did not affect the quality and functionality of the collected EVs from each kind of donor cell tested. [87] These results are promising although further studies are needed to evaluate ET on other cell types. Moreover, the development of a well-defined methodology to apply ET to a higher number of cells will contribute to the general improvement of this novel technology for EV production.…”
Section: Improving the Ev-producer Cellsmentioning
confidence: 91%
“…Indeed, given their higher flexibility in production and easier functionalization, polymersomes can be envisaged as an advantageous and cheaper alternative to liposomes. Extracellular vesicles + Difficult massive production and purification; biomolecules as only building blocks; limited tunability of the physicochemical properties [ 87,240] +++ Generally safe; extraction from biological sources with high biocompatibility [80,83] ++ Excellent loading of biomolecules; challenging loading of synthetic molecules; good delivery efficiency;rapid clearance [ 186,187] Liposomes ++ Easy production and purification; pre-and postsynthetic functionalization; tunable physicochemical properties [ 124,161] +++ Generally safe, unless modified with charged phospholipids; similar composition to EVs, but without cell-mediated modifications [103,213] ++ Good natural and synthetic molecules loading; preassembly and postassembly loading; good delivery efficiency; tunable clearance properties [ 198,199] Polymersomes +++ Customizable massive production; pre-and postsynthetic functionalization; tunable physicochemical properties [ 136,155] + Possible accumulations in the body; possibility to introduce biodegradable polymers [229,230] + Preassembly and postassembly loading; cell uptake dependent on the vesicle and cell membrane characteristic; tunable clearance properties [ 222,224]…”
Section: Productionmentioning
confidence: 99%
“…The quality of EVs exhibited no significant changes compared with the EVs secreted without electrical stimulation. In conclusion, electrical stimulation does not change the properties and/or function of EVs themselves, but accelerates the process of intracellular production and processing [63]. As shown in Figure 2, other methods that can promote EV production will be summarized in the latter part of this review.…”
Section: Indirect Drug Loadingmentioning
confidence: 97%
“…Given that the quantity of EVs secreted by natural cells falls far short of production requirements, researchers have tried to explore various ways to boost secretion amount without reducing quality. Fukuta et al found that stimulating cells with a low-level electric treatment (with a voltage of 0.34 mA/cm 2 ) for about 60 min can accelerate cell signal transduction and cell throughput, and promote the release of EVs [63]. The quality of EVs exhibited no significant changes compared with the EVs secreted without electrical stimulation.…”
Section: Indirect Drug Loadingmentioning
confidence: 99%
“…Importantly, modification of cell culture parameters has previously been shown to significantly reshape EV intraluminal cargo composition, [ 213–238 ] augment EV production (e.g., number of EVs produced per cell), [ 213,216,219,220,229,232,237,239–247 ] and increase EV potency in a diverse array of applications including neurological disorders and injuries, wound healing, cartilage repair, kidney disease, ischemia/reperfusion (I/R) injury, myocardial infarction, and sepsis. [ 53,146,215,220,222,224,229,230,232,240,241,243,247–252 ] These changes can be produced through the adjustment of numerous upstream variables including cell seeding density, [ 240 ] media composition (i.e., serum‐free media), [ 213,228,231 ] collection frequency of EVs, [ 240 ] architecture of the culture vessel (i.e., 2D vs 3D; 2D vs 3D), [ 220,222,227,229,230,239,242,243,247,248,250,253,254 ] fluid shear stress (i.e., static vs dynamic flow), [ 250,255 ] mechanical stimulation (e.g., cyclic stretch), [ 256–258 ] exposure to hypoxia, [ 143,217,219,224,228,231,232,241,245,246,251,259–265 ] heat, [ 266 ] oxidative stress, [ 225,266 ] electrical stimulation, [ …”
Section: Lessons Learned and Future Opportunitiesmentioning
confidence: 99%